2016
DOI: 10.1109/access.2016.2580680
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coherent Open-Loop MIMO Communications Over Temporally-Correlated Channels

Abstract: This paper investigates the use of non-coherent communication techniques for open-loop transmission over temporally-correlated Rayleigh-fading MIMO channels. These techniques perform data detection without knowing the instantaneous channel coefficients. Three non-coherent Multiple Input Multiple Output (MIMO) schemes, namely, differential unitary space-time modulation, differential spacetime block code, and Grassmannian signaling, are compared with several state-of-the-art training-based coherent schemes. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In any case, when the number of antennas at the BS is very large, the design of constellation and/or code blocks for all these techniques becomes unaffordable. In [34], a comparison of different schemes is provided, where only two and four transmit antennas are taken into account. For this setting, the results show that GC slightly outperforms the other schemes in low-Doppler shift scenarios.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…In any case, when the number of antennas at the BS is very large, the design of constellation and/or code blocks for all these techniques becomes unaffordable. In [34], a comparison of different schemes is provided, where only two and four transmit antennas are taken into account. For this setting, the results show that GC slightly outperforms the other schemes in low-Doppler shift scenarios.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Moreover, they proposed the idea of multiplexing the data of each user equipment (UE) in the constellation domain based on a joint-symbol, which is a superposition of the symbols sent by several UEs. In the case of DL, the combination of NCDS with MIMO has been until now based on block codes [27] - [31]. However, their application requires that the channel response remains quasi-static during the transmission of a block code, and they also need a high SNR in order to provide an acceptable performance.…”
Section: Non-coherent Demodulation Schemes (Ncds)mentioning
confidence: 99%
“…Moreover, they have the problem that they are not scalable and when the number of antennas at the BS is very large, the design of these block codes becomes unaffordable. Typically, only two and four transmit antennas are taken into account [27] - [31]. More recently, the combination of beamforming and NCDS has been proposed in order to exploit the high number of antennas through compensating the path loss and enhancing the quality of the link, and spatially multiplexing the different UEs [18], [19].…”
Section: Non-coherent Demodulation Schemes (Ncds)mentioning
confidence: 99%
See 1 more Smart Citation
“…In [13], a subset of well-known non-coherent techniques, including GCs, were compared with several state-of-art trainingbased coherent schemes over temporally-correlated Rayleighfading MIMO channels in a simplified simulation setup. Such comparison showed that non-coherent schemes are meaningful alternatives to training-based communication, especially as the number of transmit antennas increases.…”
Section: Introductionmentioning
confidence: 99%